Technologies to address challenges in areas such as agriculture and water (UN New YorkUS, 2011)
Seeks to identify ways to support sustainable agriculture in developing countries through science, technology and innovation. Addresses key challenges facing smallholder farmers and presents findings and recommendations.
Keywords: AGRICULTURE